A multidimensional approach to explore the experiences with ethnic matching amongst Chinese social service practitioners in the Greater Toronto Area - Leung, Vivian W. Y.; Tan , Weijia; Chuang, Deng-Min; Tsang , Ka Tat; Lai, Daniel W. L. (My University, 2022)
In multicultural societies, social workers often work with people of diverse cultural backgrounds. As one of the strategies to facilitate social workers’ cultural competence in diverse settings, they are often matched with clients of the same or similar cultural backgrounds. This practice is called ethnic matching and is commonly utilised in ethno-specific and immigrant-serving organisations. This practice has been extensively studied in the literature and is believed to be beneficial to treatment acceptability and service quality. Nonetheless, most of the existing literature focuses on the practitioner–client dyad without taking the broader context into consideration. This study adopted a multidimensional cultural competence approach to examine Chinese practitioners’ lived experiences of serving Chinese immigrants in the Greater Toronto Area (GTA). Six focus groups were conducted (n = 34), and data were analysed using a grounded theory approach. Results show themes across four levels: (i) personal: personal experience as a motivator; (ii) interpersonal: shared culture and language as a double-edged sword; (iii) organisational: service target shifts and increased difficulty to ethnically match and (iv) community: intracommunity heterogeneity and mismatch. This study provides recommendations for social workers, educators and policymakers to consider when applying ethnic matching in cross-cultural settings.
Keywords: Chinese; cultural competence; ethnic matching; ethno-specific service; immigrant; organisation